NILAI SIRI’ SEBAGAI POLA ASUH TERHADAP REMAJA PUTRI - Indrayanti Indrayanti; Imelda Duma (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Indonesia Timur, 2020)
ABSTRACT The value of siri 'is a philosophy of life for the people of South Sulawesi that has existed since ancient times. Siri 'is defined as a feeling of shame in doing things that are contrary to the prevailing rules in society. South Sulawesi still upholds the value of siri 'primarily to women. This is because the Bugis consider women a symbol of self-esteem in the family. Therefore, the family should look after their children to maintain the family siri ', especially girls so they don't do things that are embarrassing or tarnish the family's good name. This study aims to determine why families instill the value of siri 'primarily in adolescents and how families instill siri' values ​​in their families, especially in young women. The methodology used in this study is a qualitative method by conducting in-depth interviews with three informants, namely the teenager from South Sulawesi. The results found were that families instilled siri values' in young women in addition to continuing the value of siri 'in the family as well as maintaining siri' values ​​in the family and for its application, it was carried out as early as possible to their daughters.